Effects of Anticoagulant Treatment on the Incidence of New Vascular Events in Patients with Behcet's Disease with Vascular Involvement - Alibaz-Oner, Fatma; Karadeniz, Asli; Yilmaz, Sema; Balkarli, Ayse; Kimyon, Gezmis; Yazici, Ayten; Onat, Ahmet Mesut (Wiley-Blackwell, 2014)
…
Bilgin, Emre/0000-0002-2260-4660; erken, eren/0000-0001-6902-624X;
WOS: 000344384905427